Layer-by-layer assemblies of biopolymers: Build-up, mechanical stability and molecular dynamics - Campbell, Jack; Vikulina, Anna S. (Polymers, 2020)
Rapid development of versatile layer-by-layer technology has resulted in important breakthroughs in the understanding of the nature of molecular interactions in multilayer assemblies made of polyelectrolytes. Nowadays, polyelectrolyte multilayers (PEM) are considered to be non-equilibrium and highly dynamic structures. High interest in biomedical applications of PEMs has attracted attention to PEMs made of biopolymers. Recent studies suggest that biopolymer dynamics determines the fate and the properties of such PEMs; however, deciphering, predicting and controlling the dynamics of polymers remains a challenge. This review brings together the up-to-date knowledge of the role of molecular dynamics in multilayers assembled from biopolymers. We discuss how molecular dynamics determines the properties of these PEMs from the nano to the macro scale, focusing on its role in PEM formation and non-enzymatic degradation. We summarize the factors allowing the control of molecular dynamics within PEMs, and therefore to tailor polymer multilayers on demand.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Degradation; Diffusion; Film growth; Polyelectrolyte multilayers; Thin films